Public awareness on application of 5s’s concept at site construction in Hospital Tuanku Fauziah, Kangar, Perlis - Nurul Shahirah, Mohd Sharif (Universiti Malaysia Perlis (UniMAP), 2013)
Access is limited to UniMAP community.